2020
DOI: 10.1002/jmv.26045
|View full text |Cite
|
Sign up to set email alerts
|

Systematic analysis of ACE2 and TMPRSS2 expression in salivary glands reveals underlying transmission mechanism caused by SARS‐CoV‐2

Abstract: Coronavirus disease 2019 (COVID-19) is a global pandemic that has caused severe health threats and fatalities in almost all communities. Studies have detected severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in saliva with a viral load that lasts for a long period. However, researchers are yet to establish whether SARS-CoV-2 can directly enter the salivary glands. Therefore, this study aimed to assess the presence of angiotensin-converting enzyme 2 (ACE2)/transmembrane serine proteases 2 (TMPRSS2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(111 citation statements)
references
References 30 publications
4
99
0
8
Order By: Relevance
“…In addition, the expression of CD147, the suggested alternative receptor for SARS-CoV-2 [113], is positively correlated with the BMI possibly contributing to the COVID-19 morbidity and severity patterns [135]. Moreover, the protease TMPRSS2 is expressed in AT, though at a low level [136], while furin is enhanced expressed in obese AT as well as during adipogenesis [137]. Furin supports not only the entry of SARS-CoV-2 into cells, but also the exit of virus particles from cells by priming the spike protein [138].…”
Section: Sars-cov-2 Receptors Proteases Adipose Tissue and Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the expression of CD147, the suggested alternative receptor for SARS-CoV-2 [113], is positively correlated with the BMI possibly contributing to the COVID-19 morbidity and severity patterns [135]. Moreover, the protease TMPRSS2 is expressed in AT, though at a low level [136], while furin is enhanced expressed in obese AT as well as during adipogenesis [137]. Furin supports not only the entry of SARS-CoV-2 into cells, but also the exit of virus particles from cells by priming the spike protein [138].…”
Section: Sars-cov-2 Receptors Proteases Adipose Tissue and Obesitymentioning
confidence: 99%
“…Moreover, the protease TMPRSS2 is expressed in AT, though at a low level [ 136 ], while furin is enhanced expressed in obese AT as well as during adipogenesis [ 137 ]. Furin supports not only the entry of SARS-CoV-2 into cells, but also the exit of virus particles from cells by priming the spike protein [ 138 ].…”
Section: Obesity and Covid-19: Pathological Molecular Linkagesmentioning
confidence: 99%
“…During infection with SARS-CoV-2, it is important that the S protein of SARS-CoV-2 is cleaved by proteases, such as TMPRSS2 and furin for adsorption and fusion with the host cells [2,3,38]. Although ACE2, TMPRSS2, and furin are expressed in the oral cavity [39,40], S protein may also be cleaved by the proteases produced by periodontopathic bacteria. Therefore, periodontopathic bacteria may increase the infectivity of SARS-CoV-2.…”
Section: The Protease Of Periodontopathic Bacteria May Promote Infectmentioning
confidence: 99%
“…Its well known that SARS-CoV-2 infects host cells, including those in the respiratory tract lining, mainly using ACE2 receptor. 53 It is reported that SARS-CoV spike protein S has a high affinity for the ACE2 receptor and is activated by host type II transmembrane serine protease TMPRSS2 on primary target cells to fulfil viral entry 54…”
Section: Saliva Mark Of Sars-cov-2 Cell-receptor Features In Covid-19mentioning
confidence: 99%